CODE MIXING USED BY WARREN HUE IN VOLIX MEDIA YOUTUBE CHANNEL - Ni Putu Devi Ananda Pertiwi; I Nyoman Muliana (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2026)
This study aims to discuss the code mixings used in social media, especially the types and the reasons of using them.  This research used qualitative method, in which the data were analyzed by the theory of code mixing by Muysken (2000) to describe the types of code mixing, and the theory of Nababan (1984) to describe the reasons for using code mixing. The data were collected from Warren Hue in Volix Media Youtube Channel. This research was done by applying three steps, 1) collecting the data by watching the video, 2) transcribing the video conversation to find the utterance where the code mixing occurs, 3) sorting the data and analyzing them based on the theories applied. The results shows that there were three types of code mixing found, which were insertion, alternation, and congruent lexicalization. It was also found that there were three reasons for using code mixing, which were 1) for fun or informal situation, 2) the absences for inappropriate expressions, and 3) for showing language skills.